The limiting process in steam methane reforming with gas diffusion into a porous catalytic wall in a flow reactor. (3rd August 2015) - Saito, Motohiro; Kojima, Junichi; Iwai, Hiroshi; Yoshida, Hideo
Abstract: For a reaction in a channel with a catalytic wall, transport phenomena are important not only in the gas phase but also within the catalyst layer. This research provided a direct method for obtaining the reaction rate of steam methane reforming by taking into account the internal diffusion of the porous catalyst on the channel wall. In the experiment with different thicknesses of nickel-based catalyst, the limiting modes were observed by means of the concentrations at the interface between the gas flow and the catalyst layer. According to interpretation of the experimental results using one-dimensional diffusion equation perpendicular to the flow direction, a power-law-type reaction rate with an upper limit was found to be appropriate for explaining the region where the reaction was saturated. Finally, a versatile criterion for the rate-limiting condition was proposed through an analytical discussion based on dimensionless numbers. Highlights: A method for obtaining the reaction rate of steam methane reforming on a catalytic wall is proposed. Limiting modes were observed by the concentrations at the surface of catalyst layer. One-dimensional diffusion equation was used for modeling reaction phenomena. A power-law-type reaction rate with an upper limit can describe the reaction saturated region. A nondimensional versatile criterion for the rate-limiting condition was derived.